Of capital and power: Italian late-colonial policies in Eritrea at the onset of the federation with Ethiopia - Luca Puddu (The Journal of European Economic History (JEEH), 2021)
Scholars of African history have often inquired into the relationship between government and business in the making of North-South relations after decolonization. The neo-colonial thesis maintained that the metropolitan governments undertook overt and covert actions to preserve the dominant position of their own multinational corporations in the newly independent African nations. Historians of British Africa have partially revisited this thesis, suggesting a more nuanced understanding of the relationship between political and economic actors. This article seeks to test these arguments in relation to the Italian case, looking at the early process of decolonization in Eritrea. In 1952, the former Italian colony passed from British to Ethiopian rule, but Italian companies maintained the dominant position they had enjoyed for decades. The analysis of the relationship between the Italian authorities, Italian companies and African administrations in Ethiopia and Eritrea suggests that government intervention was crucial to support the positions of Italian capital in the former colonies, at least in the first few years of the Federation of Eritrea with Ethiopia. But it also shows that this alliance was possible only thanks to the subjugation of the needs of capital to those of raison d'état. Methodologically, the article is based on material from the historical archives of the Bank of Italy, those of the Italian Ministry of Foreign Affairs, the national archives of the United Kingdom, and the historical archives of the Italian bank Banco di Roma.
Keywords: 330